Advances in Marine Engineering: Geological Environment and Hazards - Liu, Xiaolei; Stoesser, Thorsten; Guo, Xingsen (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
With the continuous advancement of coastal, offshore, and deep-sea engineering construction (e.g. marine oil, gas, and mineral resource development, offshore wind power projects), associated studies on marine geological environments and hazards have also advanced in parallel. This reprint"Advances in Marine Engineering: Geological Environment and Hazards" is formed by a Special Issue (SI) that was organized by Prof. Xiaolei Liu from the Ocean University of China, Prof. Thorsten Stoesser from the University College London, and Dr. Xingsen Guo from the University College London to document research advances in the topics of marine engineering, including marine geological environments, marine geological hazards, marine engineering geology, marine hydrodynamics, marine fluid mechanics, and marine geotechnical engineering. The high-quality papers collected in this book involve many classic and innovative methodologies in this research field, including but not limited to analytical and statistical analyses, numerical simulations, laboratory testing, and marine surveys. The book represents the state-of-the-art in the latest research concepts, advanced methods, and data that will contribute greatly to the development of the field of marine geological environments and hazards.